STUDENT’S PERCEPTION TOWARDS THE USE OF GOOGLE CLASSROOM IN TEACHING READING - Leo Tamariska; Sri Handayani (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2021)
The aims of this research are to find out: (1) the activities carried out towards the use of Google Classroom at the eighth grade students of SMPN 1 Colomadu in academic year 2020/2021, (2) the students perceive the application and the level of students’ perception towards the use of Google Classroom at the eighth grade students of SMPN 1 Colomadu in academic year 2020/2021, (3) the students’ respond towards the use of Google Classroom in teaching reading at the eighth grade students of SMPN 1 Colomadu in academic year 2020/2021. A descriptive qualitative research method is applied in this research. The sources of the data were an English teacher and the eighth grade students of SMPN 1 Colomadu 2020/2021 academic year which is consists of 30 students. The technique of collecting data used by the researcher were an interview with the teacher and a questionnaires that distributed in Google form via link sent by WhatsApp. Meanwhile to analyze the data, the researcher used a qualitative data analysis and likert scale. The results of this research shows that the students gave a positive responses towards the use Google Classroom in teaching reading. It can be proofed by (1) most of the students were utilizing the Google Classroom well, they felt comfortable and enjoy with the Google Classroom learning style and they became interested when the Google Classroom applied in the teaching process. (2) the students perceive usefulness from the use of Google Classroom in teaching and learning process. (3) the high Google Classroom’s usage level and many students are helped by Google Classroom in their reading mastery level. It can be concluded that the use of Google Classroom have a positive impact to the student’s reading ability at the eighth grade students of SMPN 1 Colomadu in 2020/2021 academic year.   Keywords: Perception, Google Classroom, Teaching Reading, Online Learning